THE IMPORTANCE OF BREAST SELF-EXAMINATION AS A DIAGNOSTIC METHOD OF BREAST CANCER - Basegio, Diógenes Luiz; Corrêa, Maria Paula Alves; Kuiava, Victor Antonio; Quadros, Camila de; Mattos, Marina Pimentel Beber de; Pavan, Nathalia Regina; Mattiello, Júlia Mognon; Santos, Manuela Meinhardt Pinheiro dos; Garcia, Ana Luiza da Silva; Duarte, Evandro Yan; Bortolotti, Pillar (Mastology, 2019)
Method: An observational, retrospective, descriptive and cross - sectional study was carried out with data collected from Clínica Basegio, Brazil. The objective of this study was to analyze the importance of breast self-examination (BSE) as a diagnostic method for breast cancer in Passo Fundo, Rio Grande do Sul. A total of 320 patient records were selected from 1987 to 2017, among which 14 were excluded due to insufficient information. Results: BSE accounted for 48% of breast cancer diagnoses, followed by mammography and ultrasound. Imaging methods proved to be more effective in diagnosing early stage disease, while BSE detected more advanced tumors. This data was based on the histological characteristics of the tumors, with a significant difference (p<0.05) between tumor size and lymph node involvement when compared to BSE and imaging methods. Thus, the survival of the patients diagnosed by mammography and ultrasound was significantly higher than the patients diagnosed by BSE. Conclusion: Evidence from this retrospective study suggests that BSE is the prevalent diagnostic method for breast cancer in the State of Rio Grande do Sul. Despite detecting tumors in advanced stages, it is still a fundamental method within the Brazilian reality.